CYTOTOXICITY EFFECT OF AQUEOUS EXTRACT OF BRASSICA RAPA ROOTS ON CANCER CELL LINES IN VITRO - Barakat, Nadia; Obaid, Hind; Ali, Amal; Hassan, Aiman; Abaas, Zainab (Iraqi Journal of Science, 2024)
Effect of aqueous extract of Brassica rapa roots on three types of cancer cell lines; Hep-2, AMN-3 and Hela was studied in vitro.The results showed that, the cytotoxic effect of extract dependent on type of cells, amount of dose and exposure time.The concentration 1250 μg/ml gave higher growth inhibition , were ( 63 and 42 ) % to ANM-3 and Hep-2 respectively comparied with control 100% after 24 hours from exposure time , but inhibition gowth of Hela cells was 64% by 10000 μg/ml crud roots extract for 24 hours.Exposure time for 48 hours reduced the percentage of inhibited growth٫ only by10000 μg/ml for extract; viability was 25 % for ANM-3 cells.Crud aqueous extract of Brassica rapa roots was have hormetic effect ( Hormesis ), because also induced the proliferation of cancer cells by used low concentration of extract after 72 hours exposure time.